Nonlinear Radiative Treatment of Hydromagnetic Non-Newtonian Fluid Flow Induced by a Nonlinear Convective-Boundary-Driven Curved Sheet With Dissipations and Chemical Reaction Effects - Sanni, Kehinde Musodiq; Asghar, Saleem; Rashid, Saima; Chu, Yu-Ming (Frontiers in Physics, 2021)
This study investigates the flow of heat and mass transport of an incompressible MHD Cross fluid over a nonlinear curved stretching sheet. Heat transport incorporates viscous dissipation, radiative flux, and surface heating, whereas the fluid concentration is distressed with the first-order chemical reaction. A radially varying applied magnetic field is considered to examine the effect of Lorentz force and Ohmic heating. The rheology of the fluid is theoretically modeled and constitute a novel work for the completeness of shear thinning and thickening fluids over curved structure. Similarity method is utilized to reduce the governing system of PDE’s into ODE’s. Numerical computation through Runge-Kutta fourth order with shooting technique is implemented by the first initialized higher-order system into the first ODEs. The behaviors of the flow quantities—velocity, temperature, and concentration—are graphically analyzed against the parameters, including radius of curvature, fluid rheology, radiation, and rate of reactions. The numerical results are validated in comparison with the published results. Studies of Newtonian fluids on flat and curved surfaces are the special cases of this work. The results are useful in material processing and polymer dynamics involving stretchable materials.